Select the product of (9x - 6)(7x + 9).

(9x - 6)(7x + 9) = 63x^2 + 81x - 42x - 54 = 63x^2 + 39x - 54

Question

Asked 11/30/2014 8:28:39 PM

Updated 11/30/2014 9:55:59 PM

1 Answer/Comment

Edited by andrewpallarca [11/30/2014 9:54:57 PM]

s

Rating

8

(9x - 6)(7x + 9)

= 63x^2 + 81x - 42x - 54

= 63x^2 + 39x - 54

= 63x^2 + 81x - 42x - 54

= 63x^2 + 39x - 54

Added 11/30/2014 9:55:59 PM

This answer has been confirmed as correct and helpful.

How would you evaluate this one?
2 - 4{ 18 - 4[ 6 + 7(8 - 1)]}

Question

Updated 11/25/2014 11:19:58 PM

1 Answer/Comment

Select the product of (6x + 5)(x2 - 2x + 1).

Question

Updated 12/1/2014 10:12:42 PM

1 Answer/Comment

(6x + 5)(x^2 - 2x + 1)

= 6x*x^2 + 5*x^2 - 2x*6x - 2x*5 + 6x + 5

= 6x^3 + 5x^2 - 12x^2 - 10x + 6x + 5

= 6x^3 - 7x^2 - 4x + 5

= 6x*x^2 + 5*x^2 - 2x*6x - 2x*5 + 6x + 5

= 6x^3 + 5x^2 - 12x^2 - 10x + 6x + 5

= 6x^3 - 7x^2 - 4x + 5

Added 12/1/2014 10:12:42 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [12/7/2014 9:33:47 AM]

Select the product of (6x + 5)(x2 - 2x + 1). **Weegy:** (6x + 5)(x^2 - 2x + 1)
= 6x^3 - 12x^2 + 5x^2 + 6x - 10x - 5
= 6x^3 - 7x^2 - 4x + 5 (More)

Question

Expert Answered

Updated 11/30/2014 9:57:18 PM

0 Answers/Comments

Select the product of (3x - 3)(3x - 3). **Weegy:** (3x - 3)(3x - 3)
= 9x^2 - 9x - 9x + 9
= 9x^2 - 18x + 9 **User:** Select the product of . (3x+7)*(7x-3) (More)

Question

Expert Answered

Updated 11/30/2014 9:55:49 PM

0 Answers/Comments

Select the product of (-6x8y)(x5y7). **Weegy:** (-6x^8y)(x^5y^7)
= -6x^13y^8
(More)

Question

Expert Answered

Updated 11/30/2014 9:56:41 PM

0 Answers/Comments

34,466,213

questions answered

S

L

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

1

P

1

L

P

1

Points 818 [Total 6691] Ratings 19 Comments 628 Invitations 0 Online

There are no comments.